How electronic payments can support the achievement of financial inclusion goals - Smolarsky, Arthur Fernandes (2021)
The access to affordable financial services is critical to poverty reduction and economic growth, that is the reason why the theme inspires public policy for many countries with the objective to foster development through access to financial services for all. Regulatory changes and technological innovation have helped the expansion of financial services, payment methods could be listed as one of the catalysts to this revolution. Our contribution to the literature is based on two pillars. First, we expand the large body of research that focuses on financial inclusion based on its definition and on the analysis of payment methods. We provide an unique analysis of the quality dimension of payments, while exploring the access and usage dimensions. Second, we provide a detailed analysis of two cases, M-Pesa, one of the most successful stories of mobile money implementation in Kenya, the world’s first country to implement a major mobile money service and PIX, the Brazilian instant payment created by the BCB that provides the possibility to transfer resources between accounts in a few seconds, any time or day. Through the literature and analyzed cases we were able to observe both best practices and possible impacts of the adoption of electronic payment methods, this way we were able to structure parallels about the expected growth of PIX and how the instant payment method can work as a tool for financial inclusion. It is important to emphasize that there are significant differences between the M-Pesa success story and the Brazilian implementation context and PIX is still taking its first steps, that is why the suggested next steps are related to exploring a larger volume of historical data to generate even more information about the impact of adopting the new payment method with regard to financial inclusion.